Molecular methods for detecting the coconut lethal disease (LD) phytoplasma in Tanzania - Mpunami, Anatolia A. (1997)
Lethal disease (LD), a phytoplasma lethal yellowing-type disease of coconut palms, is the major threat to coconut cultivation in the coastal areas of Tanzania. Two molecular approaches have been developed for early and accurate disease diagnosis. Random fragments of LD phytoplasma DNA were generated as probes for pathogen detection. LD DNA extracted from infected coconut tissue was randomly fragmented and cloned into pUC 18. Selected recombinants were labelled with DIG-dUTP and used as probes in dot-hybridizations with total DNA from LD infected palms. The probes hybridized strongly to DNA from infected palms, but there was also a significant level of background hybridization to DNA from healthy palms. The second technique used oligonucleotide primers for conserved regions of the 16S rRNA gene and variable spacer regions between 16S and 23S rRNA genes in the polymerase chain reaction (PCR). Amplification of phytoplasma rDNA was primed from LD-infected palms in Tanzania, Kenya and Mozambique, and no amplification products were obtained from healthy coconut tissue.